LOYALTY CARDS AND ITS EFFECT ON CUSTOMER RETENTION AND CUSTOMER SATISFACTION – A CASE STUDY OF ‘BIG BAZAAR’ - Bhalla, Chirag (2010)
The majority of the organizations previously benefited from domination. Consumers did not have many substitutes or preference. With the latest entries of many new organizations, the antagonism in the market place has increased. With the entry of the new organizations, the present businesses feel threatened. Nowadays, the consumers have a range of organizations as a choice. Commodities like cars are custom made for the customers. The organizations are more consumer focussed and consumer centric. The significance of the consumer was appreciated, when they started losing their consumers to their rivals owing to the better quality of the goods and services. The organizations have realized the significance of the retaining the consumers with the aim of outliving their competitors. For this reason the marketing strategies have altered considerably. It has been observed that the relationship marketing has acquired significance more than the conventional mass marketing. With the intention of consumer retention and attaining loyalty; most of the organizations have started exercising the reward schemes to promote loyalty. These types of reward schemes are advantageous for both the organization as well as the consumer. The buyer acquires reward points for making the purchases and these reward points he/she can trade in for cash/product/discount, based on the reward system for his/her subsequent shopping and the organization collects data of for the purchases done by the consumer. This information is then utilized for the promotion intention and sustains the competitive benefit. The major motivation of this investigation is to appraise the advantages of the loyalty card to the organization and the consumer, with specific research on Big Bazaar loyalty plans. This investigation demonstrates that how the organizations make great effort for competitiveness by preserving associations with their consumers.